The Economic Determinants of Crime Rate in 7 Selected Countries: A Panel Data Analysis Approach - Shafiq, Noorishah Binti; Ali, Dayang Haszelinna Abang (Asian Journal of Empirical Research, 2022)
As the statistic of crime rates has become the main concern in any parts of the world, criminologists and policymakers have focused much in preventing crime rates from rocketing. This is where the economics of crime was generated. Thus, this study employs annual panel data from 2000 to 2013 to investigate the economic determinants of crime rate in 7 selected countries. The 7 selected countries are Honduras, Venezuela, El-Salvador, Jamaica, South Africa, Colombia and Bahamas. The methodologies used included panel unit root, panel cointegration, panel granger causality and Dynamic Ordinary Least Square (DOLS). The result shows that all the variables are stationary at the first difference and are cointegrated in the long run. From panel granger causality test, there are three short run granger causality relationship exist that run from number of tourist arrivals to GDP per capita, from GDP per capita to unemployment rate and from unemployment rate to crime rate. In addition, the result of DOLS shows that there is a long run and positive relationship between unemployment rate and crime rate. Therefore, the government and the related agencies around the world need to cooperate with one another in providing or designing the best policy in reducing crime, especially in the case of homicide.